Evaluation of the Rubber Dam Use of Dentistry Students - Enes Mustafa Aşar (Selcuk Dental Journal)
Aim: The use of rubber dam is the gold standard among isolation methods in dentistry. The aim of this study is to evaluate the students' approach and knowledge level on the use of rubber dam in dentistry. Materials and Methods: In this study, a questionnaire was created with the help of an online form builder on Google. In the survey, 18 different questions were asked in the form of multiple choice and checkboxes about the use of rubber dam. The questions used in the survey were prepared by compiling from the questions asked in the literature. Survey questions were sent to 286 people online. A total of 262 students participated in the survey. Results: Participants were %43 male and 57% female. The ages of the participants are between 20-44. Of the participants, 64% stated that they did not know how to use a rubber dam, and 97% reported that they did not use a rubber dam in clinical routine. While the rate of those who never used a rubber dam was 82% in adult patients, it was 85% in pediatric patients. Despite this, 84% of the participants think that the use of rubber dam should be mandatory in vital endodontic treatments and 71% in non-vital endodontic treatments. Most of the participants find the rubber dam useful in terms of isolation success and aspiration safety. In the answers given, the lack of knowledge and education was chosen as the most common reason for not using a rubber dam. For this reason, 96% of the participants do not consider themselves sufficient in the use of rubber dam. Conclusion: The use of rubber dam has numerous clinical benefits for the physician. For this reason, necessary theoretical and practical training should be supported for the widespread use of rubber dams.